Transformational Leadership of School Principals in the Development of Islamic Education - Efendi, Daud Rahmat; Rifa'i, Andi Arif (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
The problem of this study is that Islamic educational institutions have not been optimal in forming graduates with Islamic character due to the lack of application of Islamic values and discipline. Therefore, the role of school principals with a transformational leadership style is needed, so it is necessary to further study how the transformational leadership of school principals can support the development of Islamic education. The purpose of this study is to analyze the transformational leadership role of school principals in developing Islamic education in the era of globalization and rapid scientific progress. The transformational leadership of school principals is very important in facing the challenges of Islamic education in the era of globalization. This research is a qualitative research with a descriptive approach that aims to describe and answer problems in detail at Madrasah Ibtidaiyah Ma'arif NU Karanganyar. Data was collected through observations, interviews, and documentation from teachers and students, then analyzed in depth using data reduction techniques to obtain conclusions. The results of the research show that the transformational leadership of school principals is very important in improving the quality of Islamic education by acting as a motivator, inspirer, and agent of change that shapes the character of students according to Islamic values. Through transformational leadership principles, principals can create a positive school culture, improve teacher performance, encourage innovation, and build harmonious collaboration. This leadership also helps to face the challenges of globalization without sacrificing Islamic values, with the support of facilities, human resources, and information disclosure, despite facing obstacles such as lack of training and resistance to change.